2002
DOI: 10.1111/1467-8306.00301
|View full text |Cite
|
Sign up to set email alerts
|

Wild Animals in the Garden: Conserving Wildlife in Amazonian Agroecosystems

Abstract: In this article, I draw on field research in the Peruvian Amazon to evaluate the impact of individual and regional land-use practices (hunting, forest-clearing, and fallowing) on wildlife survival. More broadly, I examine the symbolic and practical significance of the garden as a metaphor for wildlife conservation. I focus on Tambopata Province, a region containing diverse wildlife and a variety of "gardens," from swidden fields to national parks. Field data on wildlife presence in swidden gardens reveal the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 67 publications
1
31
0
2
Order By: Relevance
“…Research on modern and prehistoric people has shown that even small human populations have an impact on their local environment (e.g., James, 2004: 29-30;Naughton-Treves, 2002). Deliberate conservation of resources by people in pre-state communities may be rarer than once thought (Smith and Wishnie, 2000), and our results suggest that large game could not supply the needs of human populations over the 1300 years considered in this study.…”
Section: Discussionmentioning
confidence: 55%
“…Research on modern and prehistoric people has shown that even small human populations have an impact on their local environment (e.g., James, 2004: 29-30;Naughton-Treves, 2002). Deliberate conservation of resources by people in pre-state communities may be rarer than once thought (Smith and Wishnie, 2000), and our results suggest that large game could not supply the needs of human populations over the 1300 years considered in this study.…”
Section: Discussionmentioning
confidence: 55%
“…A wide variety of game animals forage in agricultural fields and fallows, sometimes causing significant crop losses (Balée, 1985;Balée and Gély, 1989;Berlin and Berlin, 1983;Borge and Castillo, 1997;Carneiro, 1983;Gordon, 1982;Hames, 1980;Posey, 1984;Smole, 1989;Ventocilla, 1992). In fact, in some areas, indigenous farmers plant crops in special areas or deliberately manage fallows to increase the abundance of fruit trees that attract game (Balée and Gély, 1989;Nations and Nigh, 1980) so it is not surprising that indigenous hunting in gardens and fallows has been reported frequently (Balée, 1985;Carneiro, 1970;Gordon, 1982;Hames, 1980;Herlihy, 1986;Medellín-Morales, 1990;Naughton-Treves, 2002;Nietschmann, 1972;Posey, 1985;Ross, 1978;Ruddle, 1974;Smole, 1989;Steinberg, 1998;Vickers, 1991). This paper address the relative importance of gardens and fallows as a source of game, and what role these anthropogenic habitats might play in wildlife ecology and conservation management.…”
Section: Theoretical Contextmentioning
confidence: 99%
“…Thus, foraging opportunities in agricultural areas may be critical for animals in nearby forests during seasonal food shortages, or during infrequent but potentially devastating stochastic events that decrease food availability (e.g., extreme weather events). Importantly, the presence of a game species in an area and the frequency with which it forages in a particular farm or fallow are also conditioned by spatial patterns in the surrounding vegetation at a variety of scales (Daily et al, 2003;Naughton-Treves, 2002;NaughtonTreves et al, 2003). It is also worth noting that the interactions between habitat modification and wildlife foraging patterns are mutually influential, i.e., by foraging in gardens and fallows, animals likely have an impact on the floristic composition of secondary regrowth through their role in seed dispersal, selective herbivory, and other processes.…”
Section: Ecological Characteristics Of Garden Gamementioning
confidence: 99%
“…"The Earth as Transformed by Human Action," synopsized in the Annals (B. L. Turner, Kates, and Meyers 1994), was a landmark global-scale study. More recent Annals writings have expanded emphasis on human-environment interactions in relation to biodiversity, with special attention to analysis of prospects for environmental conservation with sustainable use (Zimmerer 1999;Cowell and Dyer 2002;Naughton-Treves 2002;Jiang 2004;Voeks 2004;Byers 2005;Campbell 2007;Goldman 2009). A series of path-breaking studies of herding, livestock, and range ecology in Africa have forged significant new understandings of the coupled interactions of resource use with political and ecological changes at the local, regional, and global scales (Bassett 1988;Dougill, Thomas, and Heathwaite 1999;M.…”
Section: Coupled Human-environment Interactionsmentioning
confidence: 99%
“…Examples of this cross-cutting appear in Annals writings on nature-society relations that are integrated with significant use of environmental science (Liverman 1990;Zimmerer 1994;M. D. Turner 1999;Bassett and Koli Bi 2000;Naughton-Treves 2002;Campbell 2007;Goldman 2009;Galt 2010) and human-environment analysis that integrates the roles of policy and politics through the structuration concept (Laney 2002;Chowdhury and Turner 2006;Brenner forthcoming). In sum, the duality of discernable intra-subfield intellectual spaces is of potential heuristic and pedagogic use while it must be seen to have defining limitations (Figure 3).…”
Section: Reflection On Nature-society Geography Within the Disciplinementioning
confidence: 99%